Influência dos íons metálicos na atividade e estabilidade de (hemi)celulases e no processo de sacarificação da biomassa - Vasconcellos, Vanessa Molina de (2015)
The enzymes involved in the conversion process of lignocellulosic biomass into second generation (2G) ethanol add a high cost to the process. Studies reported in the literature indicate that some metal ions, easily found in nature, improve the activity and stability of enzymes and the biomass saccharification process when added to the enzymatic cocktail. In this context, this work aimed to evaluate the strategy of addition of metal ions in the crude enzymatic extract in order to increase the enzyme activity and stability and to improve the saccharification process. For the production of (hemi)cellulase enzymatic complex step, a selected strain of Aspergillus niger was cultivated under solid-state fermentation (SSF), submerged fermentation (SmF) and sequential fermentation (FS). Enzyme production and thermostability were evaluated also considering the effects of pretreatment (using steam-explosion and liquid-hot-water) of the sugarcane bagasse used as carbon source and inducer. For endoglucanase and xylanase enzymes, cultivation under SSF favored production when using steam-exploded and liquid-hot-water pretreated bagasse (both washed). Removal of inhibitors from the pretreated biomass employed in the cultivation media was necessary, because the presence of phenolic compounds restricted fungal growth. The findings revealed that endoglucanase and β-glucosidase produced under SSF were less prone to thermal deactivation. From these results, enzyme complex produced by SSF using the hydrothermal bagasse was selected to evaluate the influence of the divalent metal ions Ca, Co, Cu, Fe, Mg, Mn, Ni, Zn in two concentrations (2 and 10 mM) on enzymatic activity and stability. Most of the ions influenced differently the enzymatic activity and stability, at both concentrations. The most favorable influence was obtained by the Mn+2 ion, increasing by 57% the endoglucanase activity and maintaining the enzyme stable for 72 hours, besides it also showed no negative effects on β-glucosidase and xylanase. The Mn+2 ion was then selected for the saccharification of sugarcane bagasse submitted to different pretreatments. The addition of Mn2+ ion (10 mM) in the saccharification process using enzymatic extracts produced "in house" proved to be very effective by increasing the release of glucose up to 120% when using the acid pretreated bagasse (Bác). The increase was 55% for the washed exploded bagasse (BEXL) and 70% for the liquid-hot-water pretreated bagasse (BHT). Therefore, it was possible to validate that the addition of metal ions is able to positively influence the activity and stability of enzymes, and also the process of enzymatic saccharification of lignocellulose biomass.